Pengaruh Entrepreneurial education dan E-commerce Understanding Terhadap Entrepreneurial intention Melalui Penggunaan Media Sosial - Elok Rosyida Proposalia; Tuwoso; Widiyanti (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The purpose of this study is to look at how entrepreneurship education and students' awareness of e-commerce affect entrepreneurial inclinations through the usage of social media. In this study, there are two independent factors, entrepreneurial education (X1) and e-commerce understanding (X2), one dependent variable, entrepreneurial intention (Y), and a mediating variable, social media use (Z). This study employs a descriptive design with quantitative research methodologies. Respondents for this study were Fashion Department students at SMKN 1 Sooko Mojokerto and SMKN Jatirejo who had taken entrepreneurial courses. The study included 237 students who completed a questionnaire and were analyzed using structural equality modeling (SEM). The results of this study indicate that entrepreneurial education has a positive and significant effect on social media usage, e-commerce understanding does not have a positive and significant effect on social media usage, entrepreneurial education has a positive and significant effect on entrepreneurial intention, social media usage has a positive and significant effect on entrepreneurial intention, e-commerce understanding.